Point of Care Lung Ultrasound Injury Score-A simple and reliable assessment tool in COVID-19 patients (PLIS I): A retrospective study. - Lior Fuchs; Ori Galante; Yaniv Almog; Roy R Dayan; Alexander Smoliakov; Yuval Ullman; David Shamia; Ran Ben David Ohayon; Evgeny Golbets; Khaled El Haj; Jonathan Taylor; Itai Weissberg; et al. (PLoS ONE, 2022)
Background In COVID-19 patients, lung ultrasound is superior to chest radiograph and has good agreement with computerized tomography to diagnose lung pathologies. Most lung ultrasound protocols published to date are complex and time-consuming. We describe a new illustrative Point-of-care ultrasound Lung Injury Score (PLIS) to help guide the care of patients with COVID-19 and assess if the PLIS would be able to predict COVID-19 patients' clinical course. Methods This retrospective study describing the novel PLIS was conducted in a large tertiary-level hospital. COVID-19 patients were included if they required any form of respiratory support and had at least one PLIS study during hospitalization. Data collected included PLIS on admission, demographics, Sequential Organ Failure Assessment (SOFA) scores, and patient outcomes. The primary outcome was the need for intensive care unit (ICU) admission. Results A total of 109 patients and 293 PLIS studies were included in our analysis. The mean age was 60.9, and overall mortality was 18.3%. Median PLIS score was 5.0 (3.0-6.0) vs. 2.0 (1.0-3.0) in ICU and non-ICU patients respectively (p<0.001). Total PLIS scores were directly associated with SOFA scores (inter-class correlation 0.63, p<0.001), and multivariate analysis showed that every increase in one PLIS point was associated with a higher risk for ICU admission (O.R 2.09, 95% C.I 1.59-2.75) and in-hospital mortality (O.R 1.54, 95% C.I 1.10-2.16). Conclusions The PLIS for COVID-19 patients is simple and associated with SOFA score, ICU admission, and in-hospital mortality. Further studies are needed to demonstrate whether the PLIS can improve outcomes and become an integral part of the management of COVID-19 patients.